Pembinaan Narapidana Anak Di Lembaga Pemasyarakatan Anak Klas II B Sungai Raya Pontianak - Dewi. R, Rita Rusdiana (UNIVERSITAS TANJUNGPURA, 2013)
This research aims to find out and get information clearly about coaching against the son of jail inmate Child 2B Class Sungai Raya Pontianak. The method used is descriptive method. Subjects were Trustees and child prisoners. With the source data consists of primary and secondary data sources. Data collection techniques used were observation, interview and documentation. From the analysis of the research results in general that coaching against child prisoners in Prison Children 2B Class Sungai Raya Pontianak has done well. The existence of the steps in the process of coaching, education and skills development activities have also been carried out and the response to the barriers found in the coaching process.Key Words: Development, Child Prisoners, Prisons.